Interlocked: The Ethics of Care and the Ethics of Justice in Children S Discourses on the Parent–Child Relationship in Chile - Vergara-Del Solar, A (John Wiley and Sons Inc, 2024)
The article begins with a discussion of the contribution of childhood studies to our understanding of children s ethics, taking into account feminist inputs to the debate over the ethics of care and the ethics of justice. Then, based on two qualitative studies carried out in Chile with children between 10 and 13 years of age, the article shows the emphasis the children place on reciprocal care between parents and children. This concern for reciprocity is accompanied by notions of justice and rights in how they evaluate the parent–child relationship. The data reveal the complex ways in which the ethics of care and of justice interlock in the children s discourses. The article concludes by tracing the links between these results and the conditions of productive and reproductive work in contemporary Chile as reflected in the children s discourses, and it shows how children have begun to internalise a focus on children s rights in reflecting on their daily lives. © 2024 National Children s Bureau and John Wiley & Sons Ltd.